On True Score Evaluation Using Item Response Theory Modeling. (August 2019) - Raykov, Tenko; Dimitrov, Dimiter M.; Marcoulides, George A.; Harrison, Michael
Building on prior research on the relationships between key concepts in item response theory and classical test theory, this note contributes to highlighting their important and useful links. A readily and widely applicable latent variable modeling procedure is discussed that can be used for point and interval estimation of the individual person true score on any item in a unidimensional multicomponent measuring instrument or item set under consideration. The method adds to the body of research on the connections between classical test theory and item response theory. The outlined estimation approach is illustrated on empirical data.